2018
DOI: 10.1093/femsec/fiy101
|View full text |Cite
|
Sign up to set email alerts
|

Water and sanitation: an essential battlefront in the war on antimicrobial resistance

Abstract: Water and sanitation represent a key battlefront in combatting the spread of antimicrobial resistance (AMR). Basic water sanitation infrastructure is an essential first step towards protecting public health, thereby limiting the spread of pathogens and the need for antibiotics. AMR presents unique human health risks, meriting new risk assessment frameworks specifically adapted to water and sanitation-borne AMR. There are numerous exposure routes to AMR originating from human waste, each of which must be quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
94
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(98 citation statements)
references
References 114 publications
0
94
0
4
Order By: Relevance
“…However, scientific knowledge has not yet progressed to establish the objectives for estimating the risks of ARB and ARG abundance in wastewater. Assessing the different risks to which human populations may be exposed and determining pollutants concentrations should be one of the main objectives [47]. Nonetheless, it is difficult to imagine a risk assessment framework that includes all complex gene transfer events, which may take place from environmental bacteria to human or animal pathogens [48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, scientific knowledge has not yet progressed to establish the objectives for estimating the risks of ARB and ARG abundance in wastewater. Assessing the different risks to which human populations may be exposed and determining pollutants concentrations should be one of the main objectives [47]. Nonetheless, it is difficult to imagine a risk assessment framework that includes all complex gene transfer events, which may take place from environmental bacteria to human or animal pathogens [48].…”
Section: Discussionmentioning
confidence: 99%
“…Another thing that would be valuable to measure is the rates at which the horizontal gene transfer occurs in the WWTPs. However, this is still an important knowledge gap [47]. In this sense, it has been reported that conjugation is an extremely effective mechanism for dissemination of ESBLs [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthropogenic release of antibiotic resistance genes (ARGs) into environmental reservoirs has raised global public health concerns [1,2]. The importance of wastewater treatment plants (WWTP) both as a barrier for resistant bacteria and as a potential hotspot for dissemination has been highlighted, although the evaluation of the risks for human health remains unresolved [3,4]. The increasing environmental occurrence of clinically relevant ARGs and evidence for horizontal dissemination of resistance between environmental bacteria and human pathogens demonstrate the importance of environmental resistomes (collections of resistance genes in a metagenome) [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several studies assessing multidrug resistance (MDR) in E. coli populations of animal origin, not much work has been done on the ecology of MDR [13, 14]. The spread of MDR into environments where antibiotics are not used is a possibility that has not yet been well researched, although it has been postulated that water could disseminate antimicrobial resistance [15].…”
Section: Introductionmentioning
confidence: 99%